Only One Neuron either N-bit Parity Rule Based Modified Translated Multiplicative or McCulloch-Pitts Models for Some Machine Learning Problems - Özdemir, Ali; İnal, Mehmet Melih (Prof. Dr. Ismail SARITAS, 2016)
In this study, solutions to machine learning problems such as MonkÃ¢Â€Â™s 2 (M2), Balloon and Tic-Tac-Toe problems employing a single neuron dependent on rules which use either modified translated multiplicative (ÃÂ€m) neuron or McCulloch-Pitts neuron model is proposed. Since M2Ã‚Â problem is similar to N-bit parity problem, translated multiplicative (ÃÂ€t) neuron model is modified for M2Ã‚Â problem. Also, McCulloch-Pitts neuron model is used to increase classification performance. Then either ÃÂ€m or McCulloch-Pitts neuron model is applied to Balloon and Tic-Tac-Toe problems. When the result of proposed only one ÃÂ€mÃ‚Â neuron model that is not required any training stage and hidden layer is compared with the other approaches, it shows satisfactory performance.